Strategi Penguatan Keterampilan Teknik Mengajar Bahasa Arab dalam Meningkatkan Kompetensi Bahasa Arab Siswa - Abidin, Abidin; Fadli, Adi (STAINI Press, 2025)
In the era of globalization and digital transformation, learning Arabic faces a variety of challenges, mainly due to its linguistic complexity that differs from the student's native language. Teaching technique skills are an important factor in creating effective and meaningful learning. This study uses a descriptive qualitative approach through a literature review to examine the concepts, types, and strategies of applying teaching skills in the context of Arabic language learning. The results of the study show that mastery of basic skills such as asking questions, explaining, managing classes, and providing reinforcement plays a very important role in improving students' language competence actively and contextually. The preparation of a literature-based conceptualization strategy that can be used as a practical reference in the development of the professional competence of Arabic teachers at various levels of education. The quality of Arabic learning is greatly influenced by the extent to which teachers master and apply teaching technique skills in a planned, varied, and in accordance with the main contribution of this learning process which lies in the preparation of literature-based conceptualization strategies that can be used as a practical reference in the development of professional competencies of Arabic teachers at various levels of education. The findings of this study have a positive impact on improving the quality of Arabic teaching in a sustainable manner.